Perceived stress and academic burnout among Chinese higher vocational students: The mediating roles of social support and psychological resilience - Hu, Fang; Nik Yaacob, Nik Rosila; Zhang, Fu (Journal of International Students, 2026)
This study aimed to examine the relationships between perceived stress, social support, psychological resilience, and academic burnout among Chinese higher vocational students. It explored the mediating roles of social support and psychological resilience in explaining how perceived stress influences academic burnout. A quantitative cross-sectional research design was employed, with data collected from 275 students enrolled in China higher vocational institutions. Data analysis was conducted using SmartPLS 4.0 to assess direct and mediating effects through PLS-SEM. Perceived stress had a significant positive effect on academic burnout, while it negatively influenced both social support and psychological resilience. They were found to negatively mediate the relationship between perceived stress and academic burnout, demonstrating their protective roles in reducing the adverse effects of stress. This study contributes to the growing literature on student mental health in China by integrating the Transactional Model of Stress and Coping, Stress-Buffering Model, and the Conservation of Resources Theory.